2008
DOI: 10.1063/1.2927475
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic voltage-current characteristics for a water jet plasma arc

Abstract: A virtual instrument technology is used to measure arc current, arc voltage, dynamic V-I characteristics, and nonlinear conductance for a cone-shaped water jet plasma arc under ac voltage. Experimental results show that ac arc discharge mainly happens in water vapor evaporated from water when heated. However, due to water’s cooling effect and its conductance, arc conductance, reignition voltage, extinguish voltage, and current zero time are very different from those for ac arc discharge in gas work fluid. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The overall voltage variation is like sinusoidal wave, which also appears in the gas‐phase gliding arc [ 27 ] and arc discharge in water. [ 28 ] It can be seen that the current waveform basically exhibits a sinusoidal variation, but different from the relatively stable state of the voltage waveform, the current waveform shows some differences with the propagation process of LCA discharge plasma. When LCA discharge plasma breaks down the liquid film during the propagation process, the current waveform presents a sudden increase along with the spark‐like discharge, as shown in Figure 8 with a current of about 0.5 A at 0.13 ms.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall voltage variation is like sinusoidal wave, which also appears in the gas‐phase gliding arc [ 27 ] and arc discharge in water. [ 28 ] It can be seen that the current waveform basically exhibits a sinusoidal variation, but different from the relatively stable state of the voltage waveform, the current waveform shows some differences with the propagation process of LCA discharge plasma. When LCA discharge plasma breaks down the liquid film during the propagation process, the current waveform presents a sudden increase along with the spark‐like discharge, as shown in Figure 8 with a current of about 0.5 A at 0.13 ms.…”
Section: Resultsmentioning
confidence: 99%
“…The overall voltage variation is like sinusoidal wave, which also appears in the gas-phase gliding arc [27] and arc discharge in water. [28] It can be seen that the current…”
Section: The Time-space and Electrical Characteristics Of Lca Dischar...mentioning
confidence: 99%
“…However the study of AC arc in water was less reported due to its limited applications. With the utilization of a propeller using water as a working fluid in aircraft [5] , and plasma burning technology used in wastewater treatment [6] , the study on AC arc in water has recently attracted much attention [7,8] .…”
Section: Introductionmentioning
confidence: 99%